Effects of intrinsic and extrinsic factors on intestinal parasites in a subpopulation of screaming hairy armadillo, Chaetophractus vellerosus (Xenarthra: Chlamyphoridae) from Central-Eastern Argentina - Pagnutti, Noralí (2026)
Environmental stressors, host condition, and parasitic infections are closely linked, as adverse conditions may compromise individual health and increase susceptibility to parasitism. This study evaluated the influence of intrinsic (body condition) and extrinsic host factors (farm, mining activity, cattle load, and dog abundance) on prevalence and parasite load in the Endangered subpopulation of Chaetophractus vellerosus from eastern Buenos Aires Province, Argentina. Fecal samples from 45 individuals were analyzed using coproparasitological techniques, including modified Ritchie sedimentation combined with Ziehl–Neelsen staining and Willis flotation to estimate prevalence, and a McMaster chamber to quantify parasite load. Body condition was estimated using a weight-to-total length index. All samples were parasitized. Oocysts of Eimeria spp. and Cryptosporidium sp., as well as helminth eggs (Cestoda and Nematoda), were identified. Aspidodera spp., Eimeria sp. 1, and Eimeria sp. 4 showed the highest prevalences, while Eimeria spp. exhibited the highest parasite loads. None of the models were statistically significant; however, infections with Eimeria sp. 3 were the closest to significance, being more frequent in farms with low mining and cattle activity and high dog abundance. This pattern may reflect higher vegetation cover and soil moisture favoring oocyst survival. Further research is needed to disentangle the effects of specific anthropogenic pressures on host–parasite–environment interactions.